Early Childhood in the Anglosphere: Systemic failings and transformative possibilities - Moss, Peter; Mitchell, Linda (UCL Press, 2024)
Written by two leading international experts, Early Childhood in the Anglosphere offers a unique comparison of early childhood education and care services, and parenting leave, across seven high-income Anglophone countries. Peter Moss and Linda Mitchell explore what these systems have in common, including the dominance of 'childcare’ services, widespread privatisation and marketisation, and weak parenting leave. They highlight the substantial failings of these systems, and the causes and consequences of these failings. But this book is ultimately about hope, about how these failings might be made good through major changes. In other words, it is about transformation: why transformation is both necessary and possible at this particular time, what transformation might look like, and how it might happen. Part of that transformation concerns the need for new policies and structures, but even more it is about how the Anglosphere thinks about early childhood. The authors call for turning away from conceptualising early childhood services as `childcare' and marketised businesses selling commodities to parent-consumers; and for reconceptualising them as education imbued with an ethics of care, a public good available as a right to all children and families, and complemented by well-paid, individual entitlements to parenting leave. Using examples from the Anglosphere and beyond, and in a context of converging crises, the book argues that transformation of thinking, policies and structures is desirable and doable.